Interaction entre stratégies économiques et scolarisation : l’appartenance ethnique, un marqueur des pratiques éducatives ? - Alhassane Balde; Véronique Petit (Cahiers de la Recherche sur l'Education et les Savoirs)
Contrary to popular belief, the education of children of rural households in Guinea is not a homogeneous process. Schooling approaches seem to correspond to voluntary “personal” projects that are built on collective representations of various types of success, as valued by each ethnic group. In the case of the Sub-prefecture of Kanfarandé, schooling dynamics are linked to economic strategies. Therefore, the schooling of children may be seen differently by families, depending on the ethnic group to which they belong. Data collected among families show that the schooling of children fall under three type of strategies : (1) Short and late schooling. (2) Older children are kept at home to help with housework while younger siblings will benefit from early and long term schooling (3). Children are kept at home where they receive a traditional form of education until they migrate. The article will highlight the complexity of the mechanisms involved in the process of knowledge representations.